Spatial Structure of Accomodation Distribution In Belitong Unesco Global Geopark - Fitriyani E.; Wulung S.R.P.; Abdullah C.U.; Yuliawati A. K.; Rahayu A. N. E.; Fadilah M.A.N (E3S Web of Conferences)
The purpose of this study is to map the geographical distribution of lodging in Belitung, a popular tourist site that is where the spice route is being rebuilt. The amount of accommodations, which included homestays, non-star hotels, and star hotels, was examined using a variety of geographic data analysis techniques. Up till 2021, 88 lodgings were found. Additionally, according to the findings of mapping the availability of lodging, these accommodations were located in relation to region, natural conditions, and growth stages of the tourism destination, offering additional value to prepare lodging for the development of Belitong Unesco Global Geoparks.